Análise dos conteúdos de evolução, com enfoque em Aves e Dinossauros, nas coletâneas de ciências da natureza e suas tecnologias - objeto 2, aprovadas pelo PNLD 2021 - Cares, Ândrella Bugov Carvalho (Universidade Federal de São Carlos, 2022)
In the first years of Elementary School II I discovered my passion for Biology and it guided me to the present work. The PNLD (National Didactic Book Program) allowed the distribution of textbooks to all schools registered in the plan from the early years to high school. The Program underwent a modification in 2021, adapting to the New High School and the BNCC (Base Nacional Comum Curricular) which consists of a standard that defines the contents to be addressed, defining curricula and skills that must be absorbed by students during their years of formation. Given this scenario, the present study aims to make an analysis regarding the new guidelines of the BNCC and its influence on the textbooks available for this new format of High School. From this perspective, the objective is to analyze the approach to the content of Evolution of Vertebrates, focusing on birds and dinosaurs present in the six collections available in the PNDL 2021. collections offered in the PNLD 2021 and identified as absent, present and partially present. The study presents results of a challenging scenario for the topic addressed, demonstrating a great divergence between the analyzed collections. Of which only one was present for all the indicators analyzed, the work “Matter, energy and life: An interdisciplinary approach” - Mortimer et al. (2020). Regarding the indicators of the other works, there was an oscillation between present, partially present and absent, the latter being more evident in the content that concerns the evolution of living beings, in the reptiles and birds groups, totally absent in some works.
Analysis of the contents of evolution focusing on Aves and Dinosauria, in the Natural Sciences and its Technologies - Object 2 collections approved by the PNLD 2021
Keywords: Livro didático; Sistemática Filogenética e Taxonomia; Ensino de Biologia; Textbook; Phylogenetic Systematics and Taxonomy; Biology teaching; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO